Cholesterol Crystals and NLRP3 Mediated Inflammation in the Uterine Wall Decidua in Normal and Preeclamptic Pregnancies - Silva, Gabriela Brettas; Gierman, Lobke Marijn; Rakner, Johanne Johnsen; Stødle, Guro Sannerud; Mundal, Siv Boon; Thaning, Astrid Josefin; Sporsheim, Bjørnar; Elschot, Mattijs; Collett, Karin; Bjørge, Line; Aune, Marie Hjelmseth; Thomsen, Liv Cecilie Vestrheim; et al. (Frontiers in Immunology, 2020)
Preeclampsia is a hypertensive and inflammatory pregnancy disorder associated with cholesterol accumulation and inflammation at the maternal-fetal interface. Preeclampsia can be complicated with fetal growth restriction (FGR) and shares risk factors and pathophysiological mechanisms with cardiovascular disease. Cholesterol crystal mediated NLRP3 inflammasome activation is central to cardiovascular disease and the pathway has been implicated in placental inflammation in preeclampsia. Direct maternal-fetal interaction occurs both in the uterine wall decidua and at the placental surface and these aligned sites constitute the maternal-fetal interface. This study aimed to investigate cholesterol crystal accumulation and NLRP3 inflammasome expression by maternal and fetal cells in the uterine wall decidua of normal and preeclamptic pregnancies. Pregnant women with normal (n = 43) and preeclamptic pregnancies with (n = 28) and without (n = 19) FGR were included at delivery. Cholesterol crystals were imaged in decidual tissue by both second harmonic generation microscopy and polarization filter reflected light microscopy. Quantitative expression analysis of NLRP3, IL-1β and cell markers was performed by immunohistochemistry and automated image processing. Functional NLRP3 activation was assessed in cultured decidual explants. Cholesterol crystals were identified in decidual tissue, both in the tissue stroma and near uterine vessels. The cholesterol crystals in decidua varied between pregnancies in distribution and cluster size. Decidual expression of the inflammasome components NLRP3 and IL-1β was located to fetal trophoblasts and maternal leukocytes and was strongest in areas of proximity between these cell types. Pathway functionality was confirmed by cholesterol crystal activation of IL-1β in cultured decidual explants. Preeclampsia without FGR was associated with increased trophoblast dependent NLRP3 and IL-1β expression, particularly in the decidual areas of trophoblast and leukocyte proximity. Our findings suggest that decidual accumulation of cholesterol crystals may activate the NLRP3 inflammasome and contribute to decidual inflammation and that this pathway is strengthened in areas with close maternal-fetal interaction in preeclampsia without FGR.